PENGARUH KUALITAS PELAYANAN DAN EXPERIENTAL MARKETING TERHADAP WORD OF MOUTH MELALUI KEPUASAN PADA WISATA PULAU MERAH BANYUWANGI - Niken Riska Indriani; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABTRACKThis study aims to analyze the effect of service quality and experiential marketing on word of mouth through satisfaction with Banyuwangi Red Island tourism. This research was held in Malang city. The sampling technique used was sampling purposive technique. Respondents in this study were Banyuwangi students who were in Malang city with a total of 90 respondents. This research is quantitative research and data analysis method using path analysis. The results of this study indicated  that partially service quality and experiential marketing variables indirectly have a non-significant effect on word of mouth, service quality and experiential marketing variables have a significant positive effect on satisfaction smaller than 0.05 or 5%.Keywords: service quality, experiental marketing, word of mouth, saticfaction